Factors predicting failure of empirical antibiotic therapy in neonatal sepsis in the first one week of life - Gauchan, Eva; Basnet, Sahisnuta; Malla, Kalpana Karmacharya (Journal of Chitwan Medical College, 2021)
Background: World Health Organization recommends ampicillin and gentamicin as empirical antibiotics for treatment of neonatal sepsis. However not all neonates respond to the empirical antibiotics. This study was conducted to find out the risk factors associated with treatment failure to these antibiotics so that alternative antibiotics can be started at the outset to ensure a successful discharge from hospital. Methods: A prospective, observational study was conducted in the neonatal intensive care unit of a tertiary-level hospital of Western Nepal from January 15 2019 to January 14 2020. Neonates < 7 days old with neonatal sepsis were enrolled into the study. Babies who died or whose antibiotics were changed from the empirical antibiotics to second-line antibiotics within 48 hours were classified as treatment failure. Various parameters were compared between the treatment failure group to the group who did not fail on the empirical antibiotics. Binary logistic regression analysis was carried out keeping treatment failure as the dependent variable and various independent variables were identified which predicted the chances of treatment failure. Results: Out of 173 neonates admitted for sepsis, 19 (11%) developed treatment failure. Binary logistic regression analysis found 5 min Apgar <7 (p-value=0.005), need for vasoactive support (p-value= <.001) and culture positivity (p-value= 0.009) correctly predicted treatment failure. Conclusions: In presence of Apgar score <7 at 5 minutes, need for vasoactive support and culture positivity, it would be beneficial to start alternative antibiotics according to the local microbiological flora to minimize complications and ensure better outcome.